2016
DOI: 10.15252/embj.201694591
|View full text |Cite
|
Sign up to set email alerts
|

Young microglia restore amyloid plaque clearance of aged microglia

Abstract: Alzheimer's disease (AD) is characterized by deposition of amyloid plaques, neurofibrillary tangles, and neuroinflammation. In order to study microglial contribution to amyloid plaque phagocytosis, we developed a novel model by co-culturing organotypic brain slices from up to 20-month-old, amyloid-bearing AD mouse model (APPPS1) and young, neonatal wild-type (WT) mice. Surprisingly, co-culturing resulted in proliferation, recruitment, and clustering of old microglial cells around amyloid plaques and clearance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
127
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(137 citation statements)
references
References 137 publications
8
127
0
2
Order By: Relevance
“…Since microglia of Grn −/− mice express a RNA profile typical for MGnD, we investigated if that results in increased migration. To assess migration ex vivo , we cultured organotypic brain slices from young (P6‐7) mice as recently described (Daria et al , ; Mazaheri et al , ). In line with our previous findings, we found only baseline migration of wt microglia reflected by few migrating CD68‐positive cells detected mainly in the vicinity of the brain tissue (Fig B–D).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since microglia of Grn −/− mice express a RNA profile typical for MGnD, we investigated if that results in increased migration. To assess migration ex vivo , we cultured organotypic brain slices from young (P6‐7) mice as recently described (Daria et al , ; Mazaheri et al , ). In line with our previous findings, we found only baseline migration of wt microglia reflected by few migrating CD68‐positive cells detected mainly in the vicinity of the brain tissue (Fig B–D).…”
Section: Resultsmentioning
confidence: 99%
“…Organotypic brain slices from postnatal days 6–7 of Grn −/− and wt mice were prepared, cultured, and immunostained as described before (Daria et al , ; Mazaheri et al , ). Microglial migration was analyzed after 7 days ex vivo as described (Daria et al , ; Mazaheri et al , ). Quantification was performed in three independent experiments, each including three biological replicates (three independent slice culture dishes per animal and genotype).…”
Section: Methodsmentioning
confidence: 99%
“…In support of this hypothesis, studies examining the histology of hippocampi from AD mice show that microglia ingest Aβ and prevent plaque formation; moreover, microglia from young adults less effectively take up Aβ compared with juvenile 5xFAD mice (Daria et al, ; Hellwig et al, ). These findings support the hypothesis that microglia gradually lose their functions to attenuate Aβ over AD progression.…”
Section: Microglia Affect Ad Progressionmentioning
confidence: 95%
“…Clinical imaging and neuropathological studies have shown that microglia in the central nervous system can maintain the normal physiological activity of the brain, and the activated microglia can protect the central nervous system [22]. Microglia is closely related to amyloid in AD patients and in the brain of transgenic mice that produce amyloid plaques [23,24] There are many microglia around their amyloid plaques [25]. Simard et al ,observed that microglial cells in the activated state invade into the deposited amyloid plaques, which were also found in other experiments, and this phenomenon of invasion occurred after the formation of amyloid plaques, that is , sedimentary amyloid plaques induce microglia invasion, At the same time, experiments with APP / PS1 mice showed that microglia in the activated state could swallow amyloid plaques deposited in the central nervous system [26],transcranial ultrasonography can activate microglia, thereby promoting its ingestion of amyloid .…”
Section: Discussionmentioning
confidence: 99%